Comparison of Essential Oils Composition in Iranian Populations of Thymus kotschyanus Boiss. & Hohen. - MH Azimi; H Naghdi Badi; S Kalate Jari; V Abdossi; A Mehrafarin (Journal of Medicinal Plants, 2014)
Background: Thymus kotschyanus Boiss. & Hohen. is an Iranian medicinal plants that grows in different areas of Iran such as Mazandaran, Gilan, Azarbayejan, Kurdistan and Tehran. Objective: The objective was to identify the essential oil content and composition in 15 Iranian populations of T. kotschyanus. Methods: The essential oils content and composition of 15 Iranian populations of T. kotschyanus were studied in a randomized complete block design (RCBD) with three replications. The aerial parts of thyme populations were harvested in the full blooming stage. The essential oils contents were obtianed by clevenger apparatus. For accurate measurement of the essential oils compounds, the oil samples analyzed by gas chromatography (GC) and gas chromatography coupled to mass spectrometry (GC–MS). Results: The results showed that the populations of T. kotschyanus had significant (p<0.01) differences in respect of essential oil contents. The highest essential oil content was found in the populations of Tehran, East Azarbayjan-I and East Azarbayjan-IV. The maximum thymol content was identified in the Kordestan-I population (40.42%) and the highest content of carvacrol was related to Kerman (33.08) and Zanjan-III (30.49%) populations, respectivily. Also, the thyme populations had significantly (p<0.01) differences in essential oil compositions except of carvacrol. Generally, 23 compounds in the essential oils were identified. The main constituents were carvacrol, thymol, borneol, 1.8-cinole, cymne (ortho(, carvacrol methyl ether, (z)caryophyllene, camphor, and linalool. Conclusion: Although, the populations of T. kotschyanus were planted in the same ecological and agronomical conditions, they had significant differences in terms of phytochemical traits, which probably could be due the genetic factors.